Role of A‐Site Composition in Charge Transport in Lead Iodide Perovskites. Issue 11 (15th September 2022) - Hong, Min Ji; Labram, John G.
Abstract : As the power conversion efficiency and stability of solar cells based on metal halide perovskites continue to improve, the community increasingly relies on compounds formed of mixed cations and mixed halides for the highest performing devices. The result is that device engineers now have a potentially infinite number of compositions to choose from. While this has provided a large scope for optimization, it has increased complexity of the field, and the rationale for choosing one composition over another remains somewhat empirical. Herein, the distribution of electronic properties for a range of lead iodide perovskite thin films is mapped. The relative percentages of methylammonium, formamidinium, and cesium are varied, and the electronic properties are measured with time‐resolved microwave conductivity, a contactless technique enabling extraction of electronic properties of isolated films of semiconductors. It is found a small amount of Cs leads to larger carrier mobilities and longer carrier lifetimes and that compositions with a tolerance factor close to 0.9 generally show lower performance that those closer to 0.8 or 1.0. Abstract : The electronic properties of metal halide perovskites are measured with time‐resolved microwave conductivity, as a function of A‐site composition. It is found that a small percentage of Cs leads to a larger carrier mobility and lifetime and that compositions with a tolerance factor close to 0.9 generally show lower performance than those closer to 0.8 or 1.0.